2022
DOI: 10.3389/fphar.2021.778396
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution Study of Niosomes in Tumor-Implanted BALB/C Mice Using Scintigraphic Imaging

Abstract: The purpose of this work was to study the biodistribution of niosomes in tumor-implanted BALB/c mice using gamma scintigraphy. Niosomes were first formulated and characterized, then radiolabeled with Technetium-99 m (99mTc). The biodistribution of 99mTc-labeled niosomes was evaluated in tumor-bearing mice through intravenous injection and imaged with gamma scintigraphy. The labeled complexes possessed high radiolabeling efficiency (98.08%) and were stable in vitro (>80% after 8 h). Scintigraphic imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, to set the critical range for zeta potential (mV), biologically acceptable range kept as -10-10 mV. (43) Based on all preliminary set-up target ranges in size (nm), PDI, and zeta potential (mV), all obtained data were considered to be within the critical range. The predicted formulations were also compared with experimentally obtained data by applying the similarity test (F-score: 0.83).…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…However, to set the critical range for zeta potential (mV), biologically acceptable range kept as -10-10 mV. (43) Based on all preliminary set-up target ranges in size (nm), PDI, and zeta potential (mV), all obtained data were considered to be within the critical range. The predicted formulations were also compared with experimentally obtained data by applying the similarity test (F-score: 0.83).…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…De Silva et al successfully demonstrated the manufacture of prototypical 99m Tc conjugated niosomes through a simple and fast one-step method [ 133 ]. Their work indicated the feasibility of the developed radio-niosomes for in vivo administration, resulting in high tumour to muscle uptake.…”
Section: Specialised Niosomesmentioning
confidence: 99%
“…15 Although niosomes are chemically similar to phospholipid vesicles (liposomes), they have a number of important advantages over them, including affordability, ease of storage, and increased stability (longer shelf life). 16,17 Several radiochemical processes (direct, chelator-mediated, and encapsulation) can be used to radioactively label nanoparticulate drug delivery systems with a specific radionuclide. One approach is the encapsulation of the radionuclide on the nanocarrier during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…They have received a great deal of interest as effective nanocarriers to deliver anticancer agents, chemicals, vaccines, proteins, and genes because of their excellent drug delivery capacity, including controlled release, targeted delivery, fewer adverse effects, enhanced bioavailability, and wide formulation variability . Although niosomes are chemically similar to phospholipid vesicles (liposomes), they have a number of important advantages over them, including affordability, ease of storage, and increased stability (longer shelf life). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation